Environmental hypoxia favors myoblast differentiation and fast phenotype but blunts activation of protein synthesis after resistance exercise in human skeletal muscle. Issue 10 (19th April 2018) - Gnimassou, Olouyomi; Fernández‐Verdejo, Rodrigo; Brook, Matthew; Naslain, Damien; Balan, Estelle; Sayda, Mariwan; Cegielski, Jessica; Nielens, Henri; Decottignies, Anabelle; Demoulin, Jean‐Baptiste; Smith, Kenneth; Atherton, Philip J.; et al.
ABSTRACT: We hypothesized that a single session of resistance exercise performed in moderate hypoxic (FiO2 : 14%) environmental conditions would potentiate the anabolic response during the recovery period spent in normoxia. Twenty subjects performed a 1‐leg knee extension session in normoxic or hypoxic conditions. Muscle biopsies were taken 15 min and 4 h after exercise in the vastus lateralis of the exercised and the nonexercised legs. Blood and saliva samples were taken at regular intervals before, during, and after the exercise session. The muscle fractional‐protein synthetic rate was determined by deuterium incorporation into proteins, and the protein‐degradation rate was determined by methylhistidine release from skeletal muscle. We found that: 1 ) hypoxia blunted the activation of protein synthesis after resistance exercise; 2 ) hypoxia down‐regulated the transcriptional program of autophagy; 3 ) hypoxia regulated the expression of genes involved in glucose metabolism at rest and the genes involved in myoblast differentiation and fusion and in muscle contraction machinery after exercise; and 4 ) the hypoxia‐inducible factor‐1γ pathway was not activated at the time points studied. Contrary to our hypothesis, environmental hypoxia did not potentiate the short‐term anabolic response after resistance exercise, but it initiated transcriptional regulations that could potentially translate into satellite cell incorporation and higher force production in the long term.—Gnimassou, O., Fernández‐Verdejo, R., Brook, M., Naslain, D., Balan, E., Sayda, M., Cegielski, J., Nielens, H., Decottignies, A., Demoulin, J.‐B., Smith, K., Atherton, P. J., Fancaux, M., Deldicque, L. Environmental hypoxia favors myoblast differentiation and fast phenotype but blunts activation of protein synthesis after resistance exercise in human skeletal muscle. FASEB J. 32, 5272–5284 (2018). www.fasebj.org